2010
DOI: 10.3136/fstr.16.577
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Fatty Acid Composition of Four Different Persimmon Seeds

Abstract: This study was conducted to determine antioxidant activities in acetone, ethanol, methanol, and water extracts from the seeds of 4 persimmon cultivars. Antioxidant activities were evaluated on the basis of DPPH (1,1-diphenyl-2-picrylhydrazyl) radical-scavenging activity (RSA), ABTS (2,2-azino-bis [3-ethylbenzothiazoline-6-sulfonic acid]) RSA, and reducing power. Cheongdobansi seed extracts showed significantly higher antioxidant activities and phenolic contents than did Bongok, Fuyu, and Nishimurawase seed ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 26 publications
1
12
1
Order By: Relevance
“…The results of DPPH study in this study showed that the leaf and seed tea of persimmon are good free radical scavengers. Results of Jang et al (2010) and Akter et al (2010) also showed that Values are the mean±SD of triplicate experiments. Different superscripts in the same column followed by the values are significantly different at p<0.05.…”
Section: Antioxidant Activity Of Persimmon Seed Teamentioning
confidence: 71%
See 1 more Smart Citation
“…The results of DPPH study in this study showed that the leaf and seed tea of persimmon are good free radical scavengers. Results of Jang et al (2010) and Akter et al (2010) also showed that Values are the mean±SD of triplicate experiments. Different superscripts in the same column followed by the values are significantly different at p<0.05.…”
Section: Antioxidant Activity Of Persimmon Seed Teamentioning
confidence: 71%
“…Not only the fruits but also other parts of persimmon like leaves and seeds are found to contain different phytochemicals having nutritive and medicinal values. Persimmon seeds possess high antioxidant potential and also contain high level of unsaturated fatty acids (Jang et al, 2010). Persimmon leaf extract showed therapeutic potential to alleviate the severity of radiation-induced liver injury, hyperglycemia, hypoinsulinemia, and dyslipidemia in rats (Ashry et Huang et al (2016) indicated that persimmon leaves contained a potent protective effect on cognitive deficits induced by amyloid beta in rats.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, O2 •-derived from dissolved oxygen by PMS-NADH coupling reaction reduces the yellow dye (NBT 2+ ) to produce the blue formazan, which was measured spectrophotometrically at 560 nm. It was found that plant samples containing antioxidant molecules are able to inhibit the formation of blue formazan complex [30,31]. The decrease in absorbance at 560 nm with plant extract indicates the consumption of O2 •-in the reaction mixture.…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant properties of phenolic compounds originate from their properties of donating eto free radicals to stabilize them. Therefore, the quantity of TPC in methanolic and aqueous extracts of T. bellerica was determined ( Figure 1) in order to determine the antioxidant capacity of plant extracts (Jang et al, 2010;Sampath Kumara et al, 2012). According to Shahriar et al (2012) and Venkatesan et al (2017) hexane and chloroform extracts of Terminalia arjuna fruit (73.00 and 61.72 mg/g of GAE) and Terminalia chebula bark (28.68 and 62.68 mg/g of GAE) exhibited lower TPC in comparison to the reported values of methanolic extracts in this study.…”
Section: Total Phenolic Content (Tpc)mentioning
confidence: 99%